ANALISIS WACANA & ANALISIS WACANA KRITIS BERITA KONFLIK BURUH P.T. FREEPORT INDONESIA - D Jupriono; Andia Jingga L.P.T.; Anik Cahyaning Rahayu (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2021)
Descriptive discourse analysis (DDA) considers discourse as a bigger language unit than sentence and as merely neutral linguistic phenomenon, meanwhile critical discourse analysis (CDA) (Foucault) sees discourse as constructed linguistic practice which builds social practice to change or keep power dominance. If the focus of DDA is on cohesion-coherence of text in making the unity of textual meaning, the focus of CDA is on the totality of relation of discourse which reveals and hidden to uncover the relation of power dominance among the groups inside. In DDA conclusion of the text of Freeport mine labor conflict news is: “Intimidation act of the strike labors towards the non-strike labors has caused PT Freeport to stop the production activity”. In CDA the text of the same news will be interpreted as: “Salary range based on race discrimination in Freeport labors increases horizontal conflict which is reconciled through dialogues under the control of company, so it guarantees labor’s obedience and productivity and covers the reality at once that Freeport gets so big benefit, Freeport exploitation has destroyed environment, and Timika people are still in poverty“.